1986
DOI: 10.1021/jm00158a004
|View full text |Cite
|
Sign up to set email alerts
|

Sequentially labile water-soluble prodrugs of alprazolam

Abstract: A 1,4-benzodiazepine analogue alprazolam (1) undergoes ring-opening hydrolysis under acidic conditions to form a triazolobenzophenone (2). At a neutral pH, 2 rapidly and quantitatively cyclizes back to 1. This facile reversible reaction was utilized in developing water-soluble prodrugs of 1 in which the "solubility anchoring" acyl moieties are formyl, acetyl, succinyl, glycyl, leucyl, and gamma-aminobutyryl groups. These compounds were prepared directly from 2 and corresponding acids through DCC coupling in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…These compounds were in fact considered as water-soluble prodrugs which could undergo an enzymatic hydrolysis of the peptide bond followed by a chemical cyclization in physiological conditions to give the triazolobenzodiazepine scaffold 139 (Scheme 32). As an example, Cho et al 112 reported the use of a reversible 1,4benzodiazepine ring-opening reaction of Alprazolam.…”
Section: Synthesis Of 1-(5-chloro-2-(124-triazol-4-yl)phenyl)ketones ...mentioning
confidence: 99%
“…These compounds were in fact considered as water-soluble prodrugs which could undergo an enzymatic hydrolysis of the peptide bond followed by a chemical cyclization in physiological conditions to give the triazolobenzodiazepine scaffold 139 (Scheme 32). As an example, Cho et al 112 reported the use of a reversible 1,4benzodiazepine ring-opening reaction of Alprazolam.…”
Section: Synthesis Of 1-(5-chloro-2-(124-triazol-4-yl)phenyl)ketones ...mentioning
confidence: 99%
“…While alprazolam triazolobenzophenone was originally developed as simultaneously a metabolite and prodrug of alprazolam—cyclizing back to alprazolam at neutral pH, suffering ring‐opening hydrolysis in acidic conditions to it triazolobenzophenone counterpart—there are few reports of its seizure and it is understood that its effects are similar to those of alprazolam (Cho et al, 1986; Orsolini et al, 2020).…”
Section: Types Of Prodrugsmentioning
confidence: 99%
“…To assess brain penetration of the compunds, an ex vivo assay patterned on that used by Cho et al (1986) and Sethy et al (1987) was conducted. This ex vivo assay consisted of injection of unlabeled ligand into an animal followed by sacrifice and use of an in vitro binding assay to measure residual [3 H]QNB binding to brain homogenates.…”
Section: Ex Vivo Assaymentioning
confidence: 99%
“…1). It was hoped that a combination of in vitro and ex vivo assays (Cho et al, 1986;Sethy et al, 1987) would provide answers to these questions and allow selection of promising candidates without resorting to expensive and time consuming radiosynthesis of each compound under initial consideration.…”
Section: Introductionmentioning
confidence: 99%